Analisis Efektivitas Sistem Rujukan Berjenjang dalam Upaya Penurunan Kasus Kematian Ibu dan Bayi di Kabupaten Sukabumi Tahun 2025 - Ani Andriyani; Rindu (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Maternal and infant mortality remain significant public health challenges in Indonesia. The tiered referral system is one strategy to reduce maternal and infant mortality. This study aims to analyze the effectiveness of the tiered referral system in efforts to reduce maternal and infant mortality cases in Sukabumi Regency. This qualitative research used an observational case study approach with 10 informants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation. Analysis used SWOT (IFE and EFE matrices). The total IFE score was 2.142 (strengthdominated) and the total EFE score was 1.488. The main strength was the quality of health services (0.920), while the main weakness was the capability of health workers (0.222). The main opportunity was the availability of transportation equipment (0.465), and the main threat was the availability of SOP (0.291). The tiered referral system has not been implemented effectively. The government must be fully committed to improving maternal and child health by strengthening the referral system at all levels.